The substance [videorecording (DVD)] - Fargeat, Coralie; Moore, Demi; Qualley, Margaret; Quaid, Dennis; Kračun, Benjamin; Raffertie, 1987- (MUBI, 2025)
Elisabeth Sparkle is a former A-lister fired from her fitness TV show by studio head Harvey. A new miracle drug promises it only takes one injection and she is reborn as the gorgeous, twentysomething Sue. The only catch is her body needs to alternate -- one week as Sue, one week as Elisabeth -- or else it could have disasterous effects.